Awareness of Physical Activity as an Antidepressant Mechanism: A Literature Review - Pratama, Aditya Denny; Nisrinaa, Nadaa Nadiyah (Jurnal Kesehatan Vokasional, 2025)
Background: According to WHO (World Health Organization), mental disorders such as depression affected 300 million people and became a leading cause of disability. Depression and anxiety were parts of mental illness that were very common in the Generation Z era and could have long-term impacts on human survival.Objective: This research aimed to determine the effectiveness of physical activity as an antidepressant and quality of life improvement as an effort to build the 2045 Golden Generation.Methods: This research was a descriptive literature review study using 10 articles that were reviewed according to criteria after searching and selection from several databases, namely Biomed, Pubmed, Google Scholar and Science Direct.Results: The recommended physical activity for people with depression and anxiety was jogging with moderate and vigorous intensity twice a week, or other physical activities that required a minimum of 600 METs-minutes per week, with 150 minutes of moderate-intensity activity or more than 75 minutes of vigorous-intensity activity each week.Conclusion: The implementation of physical activity was recommended because it could reduce symptoms of depression and anxiety, as well as improve quality of life.